Reconciliation of marriage: A comparative overview of the law and practice in Bangladesh and Maldives - Hassan, Kamrul; Rasheed, Khadeeja; Abdul Hak, Nora (2020)
Reconciliation process helps both the married couples to save their existing marital relationship. The Muslim dominant societies like Bangladesh and Maldives, usually practice reconciliation process during divorce proceedings. However, this process is very rarely practised in the current legal system due to some unknown reasons. Therefore, this paper highlights on the possibility of the reconciliation process in current judicial setting. The main objective of this paper is to compare relevant laws and existing practice of reconciliation in the Family Courts of both jurisdictions. Thus, this paper adopts library research, where the study uses a legal analytical approach to examine data available from relevant books, journals, laws, reported and unreported cases, personal interviews, newspapers, conference papers, and government reports. This paper concludes that the government should take an initiative to resolve divorce issues through an effective reconciliation process. It also suggests that an affordable and accessible reconciliation process can provide the best solution to the estranged couples facing marital conflict.